Pathways of Exciton Triggered Hot‐Carrier Injection at Plasmonic Metal−Transition Metal Dichalcogenide Interface. Issue 5 (9th January 2022) - Wen, Xiewen; Wang, Weipeng; Zhang, Xiang; Chen, Hailong; Jia, Shuai; Gong, Yongji; Chen, Weibing; Wang, Yanfeng; Zhu, Hanyu; Zheng, Junrong; Ajayan, P. M.; Lou, Jun
Abstract: Surface plasmon induced hot‐carrier injection to semiconducting transition metal dichalcogenide (TMD) monolayers has been extensively studied. However, comprehensive understanding of the injection kinetics by fully considering the weak metal−TMD interaction and the TMDs' exciton formation kinetics is missing. Here, a hot‐carrier injection pathway is elucidated by systematically investigating the interfacial interaction kinetics among different plasmonic metals and TMDs. The pathway highlights the exciton formation timescale as a threshold for interfacial carrier injection, before which plasmonic hot carriers and free electron−hole pairs are relaxed incoherently across the interface. The injected hot carriers will interact with excitons to form charged quasiparticles as trions, which have extended lifetime. The pathway reveals the fundamental mechanism of the plasmonic hot‐carrier−TMD interactions, opens the possibility of controllable manipulation of hot‐carrier injection process, and allows future research toward opto‐electrical guidance of trions in metal−TMD systems. Abstract : Hot‐carrier injection pathway across the interface between plasmonic nanoparticle and transition metal dichalcogenide (TMD) monolayer is elucidated. The pathway highlights the ultrafast exciton formation timescale as a threshold for interfacial carrier injection, before which plasmonic hot carriers and free electron−hole pairs are relaxed incoherently. The injected hot carriers will interact with excitons to form charged quasiparticles as trions, which have extended lifetime.